Defining the Pluripotent Marker Genes for Identification of Teleost Fish Cell Pluripotency During Reprogramming - Li, Huajin; Xu, Wenting; Xiang, Sijia; Tao, Leiting; Fu, Wen; Liu, Jinhui; Liu, Wenbin; Xiao, Yamei; Peng, Liangyue (Frontiers in Genetics, 2022)
Pluripotency is a transient state in early embryos, which is regulated by an interconnected network of pluripotency-related genes. The pluripotent state itself seems to be highly dynamic, which leads to significant differences in the description of induced pluripotent stem cells from different species at the molecular level. With the application of cell reprogramming technology in fish, the establishment of a set of molecular standards for defining pluripotency will be important for the research and potential application of induced pluripotent stem cells in fish. In this study, by BLAST search and expression pattern analysis, we screen out four pluripotent genes (Oct4, Nanog, Tdgf1, and Gdf3) in zebrafish (Danio rerio) and crucian carp (Carassius carassius). These genes were highly expressed in the short period of early embryonic development, but significantly down-regulated after differentiation. Moreover, three genes (Oct4, Nanog and Tdgf1) have been verified that are suitable for identifying the pluripotency of induced pluripotent stem cells in zebrafish and crucian carp. Our study expands the understanding of the pluripotent markers of induced pluripotent stem cells in fish.